Two N-Terminal acetyltransferases antagonistically regulate the stability of a nod-like receptor in arabidopsis - Xu, Fang; Linster, Eric; Huber, Monika; Hell, Rüdiger; Wirtz, Markus (The plant cell, 2015)
Nod-like receptors (NLRs) serve as immune receptors in plants and animals. The stability of NLRs is tightly regulated, though its mechanism is not well understood. Here, we show the crucial impact of N-terminal acetylation on the turnover of one plant NLR, Suppressor of NPR1, Constitutive 1 (SNC1), in Arabidopsis thaliana. Genetic and biochemical analyses of SNC1 uncovered its multilayered regulation by different N-terminal acetyltransferase (Nat) complexes. SNC1 exhibits a few distinct N-terminal isoforms generated through alternative initiation and N-terminal acetylation. Its first Met is acetylated by N-terminal acetyltransferase complex A (NatA), while the second Met is acetylated by N-terminal acetyltransferase complex B (NatB). Unexpectedly, the NatA-mediated acetylation serves as a degradation signal, while NatB-mediated acetylation stabilizes the NLR protein, thus revealing antagonistic N-terminal acetylation of a single protein substrate. Moreover, NatA also contributes to the turnover of another NLR, RESISTANCE TO P. syringae pv maculicola 1. The intricate regulation of protein stability by Nats is speculated to provide flexibility for the target protein in maintaining its homeostasis.